2017
DOI: 10.1159/000486144
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence of the Positive Influence of Repetitive Transcranial Magnetic Stimulation on Speech and Language in Patients with Aphasia after Stroke: Results from a Double-Blind Intervention with Sham Condition

Abstract: Background: After a stroke, up to 20% of patients suffer from aphasia. The preferred treatment for stroke-related aphasia (SRA) is regular speech and language training (SLT). In the present study, we investigated to what extent adjuvant repetitive transcranial magnetic stimulation (rTMS) might enhance recovery. While there is growing evidence of the positive effect of adjuvant rTMS on aphasia, no study has yet been based on an Iranian sample. Method: A total of 12 patients (mean age: 55 years; right-handed; 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…The authors reported a significant time by group interaction but no P-values or CIs were reported. 145 A larger cross-over study (n=30) of low frequency rTMS (vs. sham) to the right IFG, each with subsequent 45 minutes of language therapy for 10 sessions, also showed greater improvement with rTMS compared to sham on object naming (47.4±28.3 vs. 35.3±30.1, P<0.05), object naming reaction time (12.1±4.9 vs. 13.9±5.1, P<0.01), action naming (34.8±24.6 vs. 25.9±20.4, P<0.01), and action naming reaction time (15.4±5.2 vs. 15.4±5.7, P<0.01) immediately after therapy, and lasting up to 3 months, and showed gains in functional communication. 146 Similar effects of both low and high frequency rTMS have been reported in studies of chronic post-stroke aphasia (see a Naeser et al 137 for review and Ren et al 147 for a meta-analysis).…”
Section: Rtmsmentioning
confidence: 99%
“…The authors reported a significant time by group interaction but no P-values or CIs were reported. 145 A larger cross-over study (n=30) of low frequency rTMS (vs. sham) to the right IFG, each with subsequent 45 minutes of language therapy for 10 sessions, also showed greater improvement with rTMS compared to sham on object naming (47.4±28.3 vs. 35.3±30.1, P<0.05), object naming reaction time (12.1±4.9 vs. 13.9±5.1, P<0.01), action naming (34.8±24.6 vs. 25.9±20.4, P<0.01), and action naming reaction time (15.4±5.2 vs. 15.4±5.7, P<0.01) immediately after therapy, and lasting up to 3 months, and showed gains in functional communication. 146 Similar effects of both low and high frequency rTMS have been reported in studies of chronic post-stroke aphasia (see a Naeser et al 137 for review and Ren et al 147 for a meta-analysis).…”
Section: Rtmsmentioning
confidence: 99%
“…This effect can be visualized by neuroimaging [57]. Targeting these areas (and more specifically the triangular part of the right inferior frontal gyrus (IFG)) with low-frequency, inhibitory rTMS has a positive effect on language recovery in patients with aphasia following stroke [58, 59]. An important point for rTMS application is the need to stimulate the same cortical area, and this can be achieved by using brain MRI data of the treated individual to calculate the correct positioning of the coil with new generation rTMS devices by utilizing neuronavigation techniques.…”
Section: Language and Neuromodulationmentioning
confidence: 99%
“…Studies have indicated that non-invasive brain stimulation such as repetitive transcranial magnetic stimulation (rTMS) may promote more effective language recovery after stroke [ 3 6 ]. One prevailing concept is that diminished transcallosal inhibition of the non-dominant right hemisphere following left middle cerebral artery stroke negatively affects the potential of left-hemispheric dominant language centers to recover function [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of non-invasive brain stimulation to the treatment arsenal for post-stroke aphasia may help boost treatment effects of language therapy by taking advantage of the neuromodulatory effects of rTMS. Studies combining language therapy with rTMS have shown positive results in improving language function in post-stroke aphasia [ 3 , 6 , 19 22 ]. As stated above, the majority of these studies administered inhibitory low-frequency rTMS to the unaffected right hemisphere and found language improvements, particularly with naming [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%